Ruptured ectopic pregnancy as complete hydatidiform mole: Case report and review of the literature - Athanasiou, Aikaterini; Féki, Anis; Fruscalzo, Arrigo; Guani, Benedetta; Ben Ali, Nordine (Frontiers in Surgery, 2022)
Usually, a hydatidiform mole (HM) develops inside the uterus. The occurrence of HM in ruptured tubal pregnancy is exceptional. Cases reported in the literature are scarce. In this article, a case of haemoperitoneum secondary to a ruptured fallopian tube by a complete mole is reported. A 50-year-old gravida 2, para 1 was admitted to the emergency department for acute abdominal pain. After the clinical examination, an abdominal sonography and CT scan were done, revealing the presence of an adnexal left mass associated with an important haemoperitoneum. A urine pregnancy test was done and was positive, indicating an immediate laparoscopic exploration. The laparoscopy revealed a haemoperitoneum secondary to a ruptured tubal mass. The pathological exam concluded a complete hydatidiform mole (CHM) invading the wall of the fallopian tube. Any acute abdominal pain in a potentially pregnant woman imposes first the routine realization of a pregnancy test. The occurrence of CHM in a ruptured fallopian tube is particularly rare and has exceptionally been diagnosed before the laparoscopic exploration.